Suppression of human alloreactive T cells by linear tetrapyrroles; relevance for transplantation - Dunne, Aisling; Fletcher, Jean; Creagh, Emma; Basdeo, Sharee (My University, 2016)
The main limitation to successful transplantation is the antigraft response developed by the recipient immune system, and the adverse side effects of immunosuppressive agents which are associated with significant toxicity and counter indications such as infection and cancer. Furthermore, immunosuppressants do little to prevent ischemia-reperfusion injury during the transplantation procedure itself hence there is a growing need to develop novel immunosuppressive drugs specifically aimed at prolonging graft survival. Linear tetrapyrroles derived from the breakdown of mammalian heme have been shown in numerous studies to play a protective role in allograft transplantation and ischemia-reperfusion injury; however, commercial sources of these products have not been approved for use in humans. Plants and algae produce equivalent linear tetrapyrroles called bilins that serve as chromophores in light-sensing. One such marine-derived tetrapyrrole, phycocyanobilin (PCB), shows significant structural similarity to mammalian biliverdin (BV) and may prove to be a safer alternative for use in the clinic if it can exert direct effects on human immune cells. Using a mixed lymphocyte reaction, we quantified the allogeneic responses of recipient cells to donor cells and found that PCB, like BV, effectively suppressed proliferation and proinflammatory cytokine production. In addition, we found that BV and PCB can directly downregulate the proinflammatory responses of both innate dendritic cells and adaptive T cells. We therefore propose that PCB may be an effective therapeutic drug in the clinical setting of transplantation and may also have wider applications in regulating inappropriate inflammation.
PUBLISHED
Keywords: transplantation; transplantation; Immunology, Inflammation & Infection; ALLOGENEIC TRANSPLANTATION; seaweed